The Role of Phosphate Solubilizing Bacteria in Sustainable Agriculture - Arlina, Sistika; Advinda, Linda; Chatri, Moralita; Putri, Dwi Hilda (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
The repeated and unwise use of chemical fertilizers agricultural land can cause various negative impacts such as disrupting natural microbes and losing soil fertility. Phosphate solubilizing bacteria are soil bacteria that can convert phosphate from insoluble to soluble so that it can be absorbed by plants. Phosphate solubilizing bacteria play an important role in increasing plant productivity. Although the availability of phosphorus (P) in soil is in high concentrations, only 0.1% of the total phosphorus is available to plants and represents a small portion of the total in the soil. This occurs because of the low level of solubility of phosphorus and its fixation ability in the soil with several other metal elements in the soil such as Al, Ca, Fe to form aluminum phosphate, calcium phosphate and iron phosphate. There is no availability of phosphate for plants so that the role of phosphate-soluble bacteria is needed which plays a role in providing phosphate for plants so that it can increase agricultural yields. Phosphate solubilizing bacteria have great potential as biofertilizers because they can increase the bioavailability of phosphorus for plants, promote sustainable agriculture, and increase soil fertility, and increase crop yields.